2023
DOI: 10.1177/00332941231181302
|View full text |Cite
|
Sign up to set email alerts
|

Academic Encouragement and Academic Wellbeing: Mediating Roles of Grit and Hope

Abstract: Academic encouragement provides opportunities for individuals to achieve their educational objectives and influences both academic satisfaction and academic self-efficacy of individuals. In this study, academic self-efficacy and academic satisfaction constitute academic wellbeing. There is a gap in the literature on which concepts of academic encouragement predict academic wellbeing. This demonstrates the originality of the research. In this direction, there are two main purposes in this study. The first of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Another finding directly from the model in this study is that academic grit significantly predicts school satisfaction. Studies on immigrant students (Banse and Palacios, 2018;O'Neal et al, 2016) as well as students without immigrant experience (Lan and Moscardino, 2019;Okur et al, 2023;Peker and Cengiz, 2023) have found similar results on this issue. Focusing on the level of students' academic grit in the school environment is considered important in order to increase their efforts in challenging processes and prepare them for this process (Clark and Malecki, 2019).…”
Section: Bootstrappingmentioning
confidence: 54%
“…Another finding directly from the model in this study is that academic grit significantly predicts school satisfaction. Studies on immigrant students (Banse and Palacios, 2018;O'Neal et al, 2016) as well as students without immigrant experience (Lan and Moscardino, 2019;Okur et al, 2023;Peker and Cengiz, 2023) have found similar results on this issue. Focusing on the level of students' academic grit in the school environment is considered important in order to increase their efforts in challenging processes and prepare them for this process (Clark and Malecki, 2019).…”
Section: Bootstrappingmentioning
confidence: 54%